(3GdJegjO deG aj GdehWC ef GdeYGfi hGdCSGfjOs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3jHJOF HMOjK JGSY dRjO Hf CSde s
(3BNQgG (B:s
(3hjfJgi HMOjK KGf dGHf TgGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B70 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B315) s
Keywords: (3GdMOjK h GdeUWdMs